Diseño de un plan de marketing para mejorar la gestión de ventas del almacén “Contagio Sports” en el cantón La Maná, provincia de Cotopaxi, año 2013 - Tigselema Jácome, Karina Sofía (2014)
The research work was aimed in designing a marketing plan to improve sales management in "Contagio Sports" warehouse from La Maná canton, Cotopaxi province by implementing marketing strategies, advertising, promotion, adaptation, implementation of local, and so on. The development of the research was based on an investigative methodology according to its own characteristics, so that the inductive, analytic and synthetic methods were used. On this way, investigative techniques like surveys and interview were applied to citizens and general manager respectively. In fact, primary data was obtained by applying the mentioned techniques....